Answer:
[tex]y = -4x + 2[/tex]
Step-by-step explanation:
Required
Determine the equation
From the question, we understand that, it is parallel to:
[tex]4x + y -10 = 0[/tex]
This means that they have the same slope.
Make y the subject to calculate the slope of: [tex]4x + y -10 = 0[/tex]
[tex]y = -4x + 10[/tex]
The slope of a line with equation [tex]y =mx + c[/tex] is m
By comparison:
[tex]m = -4[/tex]
So, the slope of the required equation is -4.
The equation is then calculated as:
[tex]y = m(x - x_1) + y_1[/tex]
Where:
[tex](x_1.y_1) = (2,-6)[/tex]
So, we have:
[tex]y = -4(x - 2) -6[/tex]
Open bracket
[tex]y = -4x + 8 -6[/tex]
[tex]y = -4x + 2[/tex]